2002
DOI: 10.1086/341944
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Loci Involved in Cleft Lip With or Without Cleft Palate, in Chinese Multiplex Families

Abstract: Cleft lip with or without cleft palate (CL/P) is a common congenital anomaly. Birth prevalences range from 1/500 to 1/1,000 and are consistently higher in Asian populations than in populations of European descent. Therefore, it is of interest to determine whether the CL/P etiological factors in Asian populations differ from those in white populations. A sample of 36 multiplex families were ascertained through probands with CL/P who were from Shanghai. This is the first reported genome-scan study of CL/P in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 38 publications
(45 reference statements)
9
109
1
Order By: Relevance
“…PDGF-C is a latent growth factor with proteolytic activation 1 , and the processing enzyme might be controlled by the other CLP-associated genes that may indirectly connect to PDGF-C signaling. Notably, a 30-cM region on human chromosome 4, where the PDGFC gene maps, shows strong linkage association with CLP 26 , and our unpublished clinical genetic data further suggest a potential link between PDGFC gene polymorphism and CLP. …”
mentioning
confidence: 55%
“…PDGF-C is a latent growth factor with proteolytic activation 1 , and the processing enzyme might be controlled by the other CLP-associated genes that may indirectly connect to PDGF-C signaling. Notably, a 30-cM region on human chromosome 4, where the PDGFC gene maps, shows strong linkage association with CLP 26 , and our unpublished clinical genetic data further suggest a potential link between PDGFC gene polymorphism and CLP. …”
mentioning
confidence: 55%
“…The identification of geneenvironment interactions will be greatly aided by the ongoing National Study of Birth Defects Prevention [90]. Finally, new analytic strategies are being developed and tested to identify genetic epistasis and address the known heterogeneity of genetically complex traits [91].…”
Section: The Future Looks Brightmentioning
confidence: 99%
“…Egfr, Bmp4, Bmpr1 and Folbp1) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Eight genome scans have identified regions that may potentially harbor NSCLP susceptibility genes (19)(20)(21)(22)(23)(24)(25). In 2000, Prescott et al (26) identified nine chromosomal regions that are associated with orofacial clefting in their Caucasian NSCLP sib-pair population.…”
Section: Introductionmentioning
confidence: 99%